2017
DOI: 10.7150/jca.18680
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-765 Enhances the Anti-Angiogenic Effect of CDDP via APE1 in Osteosarcoma

Abstract: Human osteosarcoma (HOS) is the most common malignancy in children and adolescents and has a heterogeneous presentation and high mortality. Previous studies have shown that microRNAs contribute to RNA silencing and post-transcriptional regulation of gene expression. Here, we showed that significantly increased expression of miR-765 with or without CDDP (Cisplatin) down-regulates APE1 expression and angiogenesis-related markers (VEGF, FGF2, TGFβ, and CD34). Further investigation showed that miR-765 modulates os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…Here, for the first time, we demonstrated that miR-765 was upregulated in the plasma of ccRCC patients after tumour resection and that ccRCC tissues had a lower expression of miR-765 than non-cancerous control tissues. MiR-765 was shown to be a tumour suppressor in osteosarcoma [23] and tongue squamous cell carcinoma [24]. Other studies indicated that miR-765 was upregulated in hepatocellular carcinoma and melanoma [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Here, for the first time, we demonstrated that miR-765 was upregulated in the plasma of ccRCC patients after tumour resection and that ccRCC tissues had a lower expression of miR-765 than non-cancerous control tissues. MiR-765 was shown to be a tumour suppressor in osteosarcoma [23] and tongue squamous cell carcinoma [24]. Other studies indicated that miR-765 was upregulated in hepatocellular carcinoma and melanoma [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…SiRNAs of LINC00673, LINC00673, miRNA mimics and inhibitors were designed and synthesized by Ruibo Guangzhou. Transfection methods are described as references [8] .…”
Section: Mirna Sirna and Plasmid Transfectionmentioning
confidence: 99%
“…xenograft specimens IHC assay were performed as described previously [8]. The IHC staining score was reviewed by an expert panel of pathologists.…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%
“…Therefore, further clarification concerning the expression pattern, roles and underlying molecular mechanisms of miRNAs in MM would provide novel clinical intervention tools for patients with this fatal malignancy. miR-765 is reportedly abnormally expressed and contributes to the tumorigenesis of many different types of human cancer, such as esophageal squamous cell carcinoma (24), osteosarcoma (25) and hepatocellular carcinoma (26). However, the expression pattern, specific roles and underlying mechanism of miR-765 in MM remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%